Glutamatergic neurometabolite levels in the caudate are associated with the ability of rhythm production - Honda, Shiori; Noda, Yoshihiro; Matsushita, Karin; Tarumi, Ryosuke; Nomiyama, Natsumi; Tsugawa, Sakiko; Tobari, Yui; Hondo, Nobuaki; Saito, Keisuke; Mimura, Masaru; Fujii, Shinya; Nakajima, Shinichiro (Frontiers in Neuroscience, 2023)
Introduction Glutamatergic neurometabolites play important roles in the basal ganglia, a hub of the brain networks involved in musical rhythm processing. We aimed to investigate the relationship between rhythm processing abilities and glutamatergic neurometabolites in the caudate. Methods We aquired Glutamatergic function in healthy individuals employing proton magnetic resonance spectroscopy. We targeted the right caudate and the dorsal anterior cingulate cortex (dACC) as a control region. Rhythm processing ability was assessed by the Harvard Beat Assessment Test (H-BAT). Results We found negative correlations between the production part of the Beat Saliency Test in the H-BAT and glutamate and glutamine levels in the caudate (r = −0.693, p = 0.002) whereas there was no such association in the dACC. Conclusion These results suggest that higher glutamatergic neurometabolite levels in the caudate may contribute to rhythm processing, especially the ability to produce meter in music precisely.